THE DEVELOPMENT OF AN AUTHENTIC ASSESSMENT MODEL FOR SECONDARY EFL TEACHERS IN INDONESIA - Erwin Rahayu Saputra, - (2019)
This study reports the design and implementation of an authentic assessment model for EFL teachers in the secondary education sector in Indonesia. This is based on the phenomenon in which authentic assessment in the Indonesian context has gained educators' interest, especially teachers', due to the intricacy in its implementation. Although the mandate of implementing authentic assessment has been issued along with the guideline, in terms of practice, most of the teachers are still confused because of the unspecific guideline resulting in the lack of understanding of the assessment. Grounded in design-based research embracing participatory research philosophy, this study was carried out to fill the contextual, theoretical, and methodological gap by conducting over a semester period of study which involved six English teachers, 228 students, and one school administrator in a vocational high school in Cimahi, West Java to engage in the process of informed exploration, enactment, and evaluation of the authentic assessment model. The data gathered from observation, interview, document analysis, and questionnaire yielded beliefs, values, opinions, and experiences, and interaction of the participants in this study in terms of authentic assessment model development and implementation. They were all analyzed using a qualitative thematic analysis. The context analysis revealed that the current language policy provided teachers with the opportunity to design and develop their authentic assessment. However, they consistently based their assessment on the traditional assessment which could not reflect the actual ability of the students because it was in the form of objective test with one shot approach. With the upport of the school, the English teachers and researcher in consultation with the students designed and developed an authentic assessment model relevant to the context of the national curriculum through a professional learning community (PLC) atmosphere. Employing collegial training and mentorship activity, the teachers could develop themselves dealing with authentic assessment in order to be better in the implementation of the model of assessment. The analysis of the actual implementation of the developed model revealed that the teachers had the capacity to develop their assessment instruments based on the guideline of the developed model. This was reflected in the positive changes in the teachers' knowledge, beliefs and practice after the process of development.